Cross-cultural adaptation and clinical validation of TIME criteria to detect potentially inappropriate medication use in older adults: methodological report from the TIME International Study Group - Bahat, Gulistan; Erdogan, Tugba; Can, Busra; Ozkok, Serdar; Ilhan, Birkan; Tufan, Asli; Karan, Mehmet Akif; Benetos, Athanase; Cherubini, Antonio; Drey, Michael; Garfinkel, Doron; Gąsowski, Jerzy; et al. (Drugs & aging, 2025)
Background Various explicit screening tools, developed mostly in central Europe and the USA, assist clinicians in optimizing medication use for older adults. The Turkish Inappropriate Medication use in oldEr adults (TIME) criteria set, primarily based on the STOPP/START criteria set, is a current explicit tool originally developed for Eastern Europe and subsequently validated for broader use in Central European settings. Reviewed every three months to align with the latest scientific literature, it is one of the most up-to-date tools available. The tool is accessible via a free mobile app and website platforms, ensuring convenience for clinicians and timely integration of updates as needed. Healthcare providers often prefer to use their native language in medical practice, highlighting the need for prescribing tools to be translated and adapted into multiple languages to promote optimal medication practices. Objective To describe the protocol for cross-cultural and language validation of the TIME criteria in various commonly used languages and to outline its protocol for clinical validation across different healthcare settings. Methods The TIME International Study Group comprised 24 geriatric pharmacotherapy experts from 12 countries. In selecting the framework for the study, we reviewed the steps and outcomes from previous research on cross-cultural adaptations and clinical validations of explicit tools. Assessment tools were selected based on both their validity in accurately addressing the relevant issues and their feasibility for practical implementation. The drafted methodology paper was circulated among the study group members for feedback and revisions leading to a final consensus. Results The research methodology consists of two phases. Cross-cultural adaptation/language validation phase follows the 8-step approach recommended by World Health Organization. This phase allows regions or countries to make modifications to existing criteria or introduce new adjustments based on local prescribing practices and available medications, as long as these adjustments are supported by current scientific evidence. The second phase involves the clinical validation, where participants will be randomized into two groups. The control group will receive standard care, while the intervention group will have their treatment evaluated by clinicians who will review the TIME criteria and consider its recommendations. A variety of patient outcomes (i.e., number of hospital admissions, quality of life, number of regular medications [including over the counter medications], geriatric syndromes and mortality) in different healthcare settings will be investigated. Conclusion The outputs of this methodological report are expected to promote broader adoption of the TIME criteria. Studies building on this work are anticipated to enhance the identification and management of inappropriate medication use and contribute to improved patient outcomes.
Online veröffentlicht: 17. Dezember 2024
Gesehen am 06.05.2025